Gender Segregation and Gender Wage Differences during the Early Labour Market Career - Peggy Bechara (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2012)
Using German linked employer-employee data this paper investigates the gender wage gap at the time of entering the labour market and its development during workers' early career. The analysis contributes to the existing research on gender wage differentials among young workers by providing evidence on the impact of women's disproportionate concentration in lower-paying industries, occupations, establishments and job-cells, i.e. occupations within establishments. The estimation results reveal that all types of segregation and particularly job-cell segregation are significant determinants of the gender wage gap, while skill endowments and differences in work histories are found to be of minor importance. At the time of labour market entry women's wage disadvantages can almost entirely be explained by the fact that they start their working career in lower-paying occupations and establishments. With progressing labour market experience, however, gender segregation becomes less important and cannot fully account for a slight widening of the wage differential among young men and women. Therefore, part of the early career wage gap remains unexplained. – – Diese Studie untersucht auf Basis von Linked-Employer-Employee Daten die Entwicklung geschlechtsspezifischer Lohnunterschiede während der frühen Karrierejahre. Die Analyse zeigt, dass die Verteilung von Männern und Frauen auf unterschiedliche Branchen, Berufe und Betriebe einen erheblichen Beitrag zur Erklärung der Lohnnachteile von Frauen leistet. Zu Beginn der beruflichen Karriere existiert zwischen Männern und Frauen, die innerhalb des gleichen Betriebes den gleichen Beruf ausüben, nahezu kein Lohnunterschied. Mit zunehmender Arbeitsmarkterfahrung geht ein Wachstum des geschlechtsspezifischen Lohndifferentials einher, welches weder durch Segregation noch durch Unterschiede in der Arbeitsmarkthistorie erklärt werden kann.
Keywords: J16; J24; J31; J62; 330; Gender wage gap; early career; labour market segregation